2015
DOI: 10.1016/j.atmosres.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Indian summer monsoon and the large-scale circulation variability over the Mediterranean

Abstract: In this study the impact of the Indian summer monsoon on the large scale variability of the atmospheric circulation over the Mediterranean is investigated on an inter-annual time scale. Composite and correlation analysis results are presented, outlining different circulation patterns in the upper and lower troposphere for strong and weak monsoon years respectively. For this purpose ERA-40 Reanalysis monthly mean data at various isobaric levels together with the standardized All India Rainfall Index for boreal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
(58 reference statements)
3
18
0
Order By: Relevance
“…Teleconnection patterns can affect vast areas (such as the Northern Hemisphere) and explain much of the variability and trends in precipitation and temperature at the regional scale (Trigo and Palutikof 2001;Vicente-Serrano et al 2006;López-Bustins et al 2008;Rizou et al 2015, Rios-Cornejo et al 2015. Some studies in Asia have also focused on the relationship between climate and patterns in recent decades: Tatli (2007) in the region 50ºW-120ºE, 0º-80ºN; Syed et al (2010) in Central -Southwest Asia; Villafuerte and Matsumoto (2015) in Southeast Asia; Khan et al (2008), Saaed et al (2011), Revadekar et al (2012) and Azfal et al (2013) in Pakistan; Khalili (2006, 2008) in Iran; Türkes and Erlat (2009) The main goal of the present study is to contribute to the existing knowledge of trends (sign and magnitude) in Tmax and Tmin in Pakistan in recent decades.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Teleconnection patterns can affect vast areas (such as the Northern Hemisphere) and explain much of the variability and trends in precipitation and temperature at the regional scale (Trigo and Palutikof 2001;Vicente-Serrano et al 2006;López-Bustins et al 2008;Rizou et al 2015, Rios-Cornejo et al 2015. Some studies in Asia have also focused on the relationship between climate and patterns in recent decades: Tatli (2007) in the region 50ºW-120ºE, 0º-80ºN; Syed et al (2010) in Central -Southwest Asia; Villafuerte and Matsumoto (2015) in Southeast Asia; Khan et al (2008), Saaed et al (2011), Revadekar et al (2012) and Azfal et al (2013) in Pakistan; Khalili (2006, 2008) in Iran; Türkes and Erlat (2009) The main goal of the present study is to contribute to the existing knowledge of trends (sign and magnitude) in Tmax and Tmin in Pakistan in recent decades.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…During summer, dry hot weather is the main climatic characteristic for the Aegean basin. Etesians contribute to the decrease of surface temperature in order to moderate the summer heat and control the appearance of heat wave events during summer as results of the mid‐tropospheric decent and the cool advection in the lower levels (Metaxas and Bartzokas, ; Ziv et al ., ; Tyrlis et al ., ; Rizou et al ., ). Etesians contribute to the reduction of pollution events, enhancing pollutant dispersion and improve air quality (Metaxas and Bartzokas, ; Melas et al ., ; Ziomas, ; Giakoumi et al ., ; Poupkou et al ., ; Tyrlis et al ., ); on the other hand, strong Etesians can enhance the fast spread of fires in the Aegean islands (Kotroni et al ., ; Amraoui et al ., ) and can cause difficulties with sea transport and sailing (Metaxas and Bartzokas, ; Koletsis et al ., ; Koletsis et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In general, Etesians can be classified as a monsoon type wind system (Poupkou et al ., ). Previous studies focused on the connection between the Etesians and the South Asia monsoon system (Tyrlis et al ., ; Tyrlis and Lelieveld, ; Rizou et al ., ; Dafka et al ., ). According to Tyrlis et al ., , the subsidence over the EMED–Middle East and the Etesian circulation over the Aegean are connected to the large‐scale ascent over the South Asian monsoon region via the westwards propagating Rossby waves (Rodwell and Hoskins, ; Tyrlis et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziv et al (2004) have shown these two factors to be significantly correlated, pointing to the Asian summer monsoon, which exerts an influence on the Mediterranean surface, middle, and upper troposphere dynamics. The possible mechanism behind this linkage was explored in a framework of the Rossby wave pattern response to the diabatic heating of the monsoon convection, i.e., the monsoondesert mechanism (Rodwell and Hoskins, 1996;Tyrlis et al, 2013;Rizou et al, 2015;Cherchi et al, 2014Cherchi et al, , 2016. Additionally, Rodwell and Hoskins (2001) explained changes in Etesian winds as a direct result of changes in the subsidence over the eastern Mediterranean, which via Sverdrup's equation controls the low-level northerly flow.…”
Section: Introductionmentioning
confidence: 99%